Phylogenetic Groups and Antimicrobial Resistance among Uropathogenic Escherichia coli Isolates from Hospitalized Patients in Tehran - Talebi Farahani, Mana; Karim Rahimi, Mohammad; Goudarzi, Mehdi (Novelty in Biomedicine, 2025)
Background: The presence of Escherichia coli among uropathogens is increasing significantly worldwide. It accounts for a considerable amount of morbidity and high medical costs and also can lead to mortality. The current research aims to investigate E. coli antimicrobial susceptibility patterns and the molecular causes of E. coli resistance trends and virulence factors among phylogenetic groups of Uropathogenic Escherichia coli (UPEC) in Urinary tract infection (UTI) patients in a hospital in Tehran, Iran. The antimicrobial susceptibility of urinary E. coli isolates. Materials and Methods: The antimicrobial susceptibility of urinary E. coli isolates was tested using the Kirby-Bauer agar disc diffusion method. In addition, resistance and virulence genes were monitored by polymerase chain reaction (PCR), and the clonal relation of isolates was studied by pulsed-field gel electrophoresis (PFGE). Results: Studied isolates showed the highest susceptibility rates to MEM (95.7%), followed by TZP (90%). In contrast, resistance rates were found for AMP (100%), SXT (74%), and CIP (51.5%). ESBL-producing isolates were positive for blaTEM, blaCTX-M, and blaSHV by PCR, respectively. According to the adhesion gene analyses, fimH (85.8%) was the most prevalent among E. coli isolates, followed by aer (49.7%), hlyA (46.1%), and pap (38.9%). A total of 57 PFGE patterns and three clusters (A–C) were identified by the PFGE method. (cluster A: Non-ESBL & Sensitive to all Antibiotics use; Cluster B: The most common cluster in terms of TEM, CTX-M, or both; Cluster C: containing CTX-M gene and resistant to ceftriaxone and ciprofloxacin). Conclusion: Our data showed ESBL rates were high in UTI E. coli isolated in the studied hospital. The UPEC isolates exhibited a high resistance rate to first- and second-generation cephalosporins and fluoroquinolone, which could result in serious public health risks. The relationship between virulence factors and resistance genes is complex and needs more studies specific to each area.